The effect of brief neonatal exposure to cows' milk on atopic symptoms up to age 5. Issue 5 (1st May 2002) - de Jong, M H; Scharp-Van Der Linden, V T M; Aalberse, R; Heymans, H S A; Brunekreef, B
Abstract : Aims: To determine the effect of brief early exposure to cows' milk on the expression of atopy during the first five years of life. Methods: Follow up analysis of a double blind, placebo controlled, randomised feeding intervention trial (BOKAAL study). Subjects were 1108 children from 1533 initially randomised breast fed neonates in the Netherlands. Atopic disease and prevalence of allergic symptoms at age 1, 2, and 5, and specific IgE at age 1 and 5 were determined. Results: Atopic disease in the first year was found in 10.0% (cows' milk) versus 9.3% (placebo) of the children, with a relative risk (RR) of 1.07. No differences were found in the second year either. At age 5, atopic disease was found in 26.3% (cows' milk) versus 25.0% (placebo), RR 1.05. There was no difference in the prevalence of allergic symptoms. Specific IgE to cows' milk (RAST positive 2+ or more) was 5.8% (cows' milk) versus 4.1% (placebo) at age 1 (RR 1.43), and 5.3% versus 3.0% at age 5 (RR 1.77). There was no difference in sensitisation to other common allergens between the two groups. Conclusion: Early, brief exposure to cows' milk in breast fed children is not associated with atopic disease or allergic symptoms up to age 5.